DATOS BIOLÓGICOS Y DESCRIPCIÓN DE ESTADOS INMADUROS DE INHUMEROCLERUS THOMSONIPIC, 1955 (COLEOPTERA: CLERIDAE: CLERINAE) - Solervicens A., Jaime; Ormazábal T., Félix (Acta Entomológica Chilena, 2022)
Inhumeroclerus thomsoni Pie, 1955 was found to occur together with xylophagous and parasitoids insects in dead plants of Euphorbia lactiflua (Euphorbiaceae) of the Coastal desert región of northem Chile. In laboratory conditions the emergence of all of the inseets associated with Euphorbia lactiflua was concentrated in spring time and the permanence of adults was very short. The adult larva and pupa of Inhumeroclerus thomsoni were described. The characters of larva are those of Cleridae discarding any possibility of inclusión in Thanerocleridae. The presence of lateral selerotized area of the maxilary mala apparently relate Inhumeroclerus thomsoni with two other Clerinae: Natalis laplacii Lap. and Thanasimodes gigas Lap. This character must be investigated as a probable larval apomorphy of the subfamily.